Modelo de gestión de calidad y atención al usuario del Gobierno Autónomo Descentralizado Municipal del cantón Bolívar - Delgado Dueñas, Erika Paola (2025)
The purpose of this research was to design a quality management model that contributes to the improvement of user service in the Decentralized Autonomous Municipal Government of the canton of Bolívar. To this end, three phases were developed: identification of the management models and methodological approaches that exist in terms of quality management, determination of the key elements of a management model for the municipal GAD of the canton of Bolívar, and the proposal of the design of a quality management model. The research was carried out through bibliographic and documentary review, complemented with techniques such as interviews and surveys. In the first phase, management models and methodological approaches were identified, based on ISO standards and suitable for decentralized autonomous governments. Within the second phase, the elements of the management model were specified from the interviews carried out in the user service areas of the GAD, in addition to a survey applied to the citizens of the canton, where it was developed through the Servqual model and the Likert scale. In the third phase of the research, the model was designed, with the purpose of improving user service, which was socialized and notified to the authorities of the GAD Bolivar, with the execution of this research, it was possible to define that there is no quality management model focused on user service. therefore, the proposal presented represents a benefit for both the institution and the citizens.